Detection of decay and hollows in living almond trees (terminalia catappa L. roxb.) using electrical resistivity method (2018)
A precise and cost-efficient diagnostic technique for detecting decay and other structural defects in living trees is indispensable for the risk assessment and conservation of urban and forest trees. A study was carried out to detect the location and extent of decay and hollows (or cavities) in almond trees (Terminalia catappa L. Roxb.) using the four-point electrical resistivity method. Electrical resistivity measurements (ERm) of randomly selected living almond trees were taken using an earth resistivity meter, four probes and a modified form of Schlumberger electrode configuration. The ERm were used to obtain resistivity profiles (RP) of the trees. The RP of freshly cut healthy, decayed and hollowed trees were also obtained. A laboratory experiment was set up to replicate the RP of healthy, decayed and hollowed trees. Wood decay and cavities in trees were detected through RP matching. In comparison to healthy trees, wood decay and cavities in tree stems were detected with relatively sharp decrease and increase in electrical resistivity values, respectively. The extent of the resistivity anomalies corresponds to the extent of wood decay and cavities in trees. This method is applicable to early detection of decay and cavities in hardwood trees.